Nowcasting Indonesia - Matteo Luciani; Madhavi Pundit; Arief Ramayandi; Giovanni Veronese (Asian Development Bank (ADB), 2015)
We produce predictions of the current state of the Indonesian economy by estimating a Dynamic Factor Model on a dataset of 11 indicators (also followed closely by market operators) over the time period 2002 to 2014. Besides the standard difficulties associated with constructing timely indicators of current economic conditions, Indonesia presents additional challenges typical to emerging market economies where data are often scant and unreliable. By means of a pseudo-real-time forecasting exercise we show that our model outperforms univariate benchmarks, and it does comparably with predictions of market operators. Finally, we show that when quality of data is low, a careful selection of indicators is crucial for better forecast performance.
hdl:11540/5299
Keywords: C32; C53; E37; O53; 330; Dynamic Factor Models; emerging market economies; nowcasting